ANTARA TAKWA DAN TAKUT (Kajian Semantik Leksikal dan Historis terhadap al-Qurâan) - Affandi, Abdullah; Suud, Muhammad (Jurnal al Hikmah, 2016)
In some approaches that occurs in Islamic studies, there is one essential that the process is seen as the most urgent and influential in the development process itself, namely Islam